2014
DOI: 10.2139/ssrn.2560739
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic Decision Making in Network Linking

Abstract: Network formation among individuals constitutes an important part of many OR processes, but relatively little is known about how individuals make their linking decisions in networks. This article provides an investigation of heuristic effects in individual linking decisions for network formation in an incentivized lab-experimental setting.Our mixed logit analysis demonstrates that the inherent complexity of the network linking setting causes individuals' choices to be systematically less guided by payof but mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Ordinal link externalities are robust in the sense that they still hold when utilities are perturbed by small error terms, e.g. as in Harmsen-van Hout et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ordinal link externalities are robust in the sense that they still hold when utilities are perturbed by small error terms, e.g. as in Harmsen-van Hout et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Harmsen-van Hout et al (2016) show experimentally that when faced with linking choices involving increased complexity of payoffs, experimental subjects resort to simplified decision rules, i.e. heuristics.…”
Section: Now Consider the Casementioning
confidence: 99%
“…2 The authors identify two factors that are related to payoffs only qualitatively, but have been used by the experimental subjects: whether or not the choice option involves a deviation from the status quo and the number of direct neighbours of the (potential) linking partner. They call for future models to include the human tendencies 3 "to base complex linking decisions on heuristic cues like... node degree rather than exact payoff" (Harmsen-van Hout et al, 2016), as found by their analysis.…”
Section: Now Consider the Casementioning
confidence: 99%
See 1 more Smart Citation